Language-sensitive lsp teaching: concepts, models and planning aids - (:unkn) unknown (Rubanets Tetyana, 2024)
The article deals with language-sensitive LSP teaching from the perspective of academic theory and, using insights from research, proposes methods for acquiring subject-specific language skills in German as an introduction to professional language. Language-sensitive subject teaching is a didactic concept of integrated subject and language learning. Subject-specific content, working methods and ways of thinking are introduced to learners through a language-conscious approach, which pays conscious attention to language in order to facilitate subject-specific learning. The article describes the peculiarities of the German professional language relevant for a better understanding of the professional language, compares the competences for mastering a foreign language and a professional language, presents two approaches to it – affective and defensive, and suggests a methodology for teaching professional knowledge in German.
Keywords: languages for specialised purposes, language-sensitive LSP teaching, basis interpersonal communicative skills, cognitive academic language proficiency, scaffolding, grids